Nested Topology Optimization Methodology for Designing Two-Wheel Chassis - Manios, Stefanos E.; Lagaros, Nikos D.; Nassiopoulos, Elias (Frontiers in Built Environment, 2019)
Weight reduction has always been a challenge for the automotive industry, mainly to reduce consumption but also improve handling. In electric vehicle design, the battery packs, their shape and positioning are critical aspects that determine the overall weight, weight distribution and, as a consequence, the efficiency, dynamics and stability of the vehicle. This presented a new challenge, to manage this necessary and inflexible weight and volume, developing the vehicle chassis around it and in the best possible way, without compromising the overall efficiency and behaviour. In this work, a methodology for nested topology optimization has been developed which combines structural topology optimization and battery pack shaping and positioning. The new methodology is implemented, without limiting its applicability, into the framework of the commercial software Hyperstudy by Altair.